2014
DOI: 10.4238/2014.december.4.16
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 mRNA expression is associated with the clinical outcome of non-small cell lung cancer treated with platinum-based chemotherapy

Abstract: ABSTRACT. We conducted a prospective study to analyze the expression of the excision repair cross-complementing group 1 (ERCC1) and ribonucleotide reductase subunit M1 (RRM1) genes in 297 Chinese patients with advanced non-small cell lung cancer (NSCLC). The goal of this study was to evaluate these genes as potential biomarkers for prediction of tumor response and clinical outcome. Patients with unresectable, locally advanced or metastatic NSCLC were enrolled between September 2007 and September 2009, and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In multivariate analysis, after adjusting for prognostic factors including mitotic index, TOP2A expression failed to be a significant independent prognostic parameter. TOP2A is a marker of cell proliferation (Zhang et al 2014) and the direct correlation of this enzyme expression with the mitotic count (although not significant) could account for its failure to be an independent prognostic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, after adjusting for prognostic factors including mitotic index, TOP2A expression failed to be a significant independent prognostic parameter. TOP2A is a marker of cell proliferation (Zhang et al 2014) and the direct correlation of this enzyme expression with the mitotic count (although not significant) could account for its failure to be an independent prognostic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐eight studies met our eligibility criteria; Figure shows the PRISMA flow diagram. These reports spanned 12 years of published research; properties of our sample are shown in Table . This study sample reflects 4,311 patient samples (2,295 tested for protein expression and 2,016 for mRNA) in total.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers 16 - 20 found that the expression of ERCC1 was associated with the clinical outcome of NSCLC treated with platinum-based chemotherapy. In a study conducted by Zhang et al 21 among 297 advanced stage NSCLC patients who were treated with platinum-based chemotherapy, it was found that ERCC1 mRNA expression levels in blood were related to the treatment response and survival time. Patients with low ERCC1 mRNA expression level in blood had a significantly higher rate of CR to chemotherapy, with an odds ratio (OR) of 1.56 (95%CI: 1.03-2.47).…”
Section: Discussionmentioning
confidence: 99%